IDENTIFIKASI GOLONGAN SENYAWA ANTI KANKER PAYUDARA IN VITRO PADA TIGA VARIETAS BUAH MERAH (Pandanus conoideus Lamk.) - Sasi Hermanto (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2011)
Abstract: Cancer was one of health problems in the world. Medical treatments of cancer by operation, chemotherapy, and radiation were really good, but they have some effects. Now, people were interested in using of natural product as medicine. Red fruit (Pandanus conoideus Lamk.) have been extensively used to treat HIV/AIDS, diabetic mellitus, uric acid, osteoporosis and cancer. The scientific studies of anti cancer activity of red fruits on the growth of cancer are relatively very few. The objective of this research was to determine the variety of Red Fruit that have the high toxicity and to identify the bioactive compound that have a cytotoxic effect on breast cancer cell line (T47D). Three samples (Maler, Barugum, and Yanggiru) were collected from Sentani (Papua). The cell line used were T47D for breast cancer and cancer drug Doxorubicine was used as a standard on cytotoxicity assay. All samples were extracted using three solvents (chloroform, methanol, and water). Anti cancer activity on breast cancer cell line of those extracts were detected using MTT Assay to determine IC-50. The best extract (lowest IC-50) was fractionated, isolated, and identified its compound group. The value of extract IC-50 and toxic isolate were calculated by probit analysis. The results showed that methanol extract of Barugum has the highest cytotoxic effect to cell line T47D (IC-50 = 170,204 μg/ml) followed by chloroform extract of Maler (IC-50 = 193,090 μg/ml). But, the isolate of fraction of Maler chloroform extract had the highest cytotoxic effect (IC-50 = 32,453 μg/ml), that is lower than Doxorubicine (49,194 μg/ml) while the isolate of methanol extract of Barugum had IC-50 = 60,298 μg/ml. The bioactive compound group that has anti-cancer activity were terpenoid saponin and other terpenoids. It could be concluded that the chloroform extract of Maler was potential to be developed as cancer medicine.Key Words: Red Fruit, cancer, T47D, cytotoxic, MTT Assay.